Plant Growth Pattern, Forage Yield, and Quality of Indigofera zollingeriana Influenced by Row Spacing - Nur Rochmah Kumalasari; G. P. Wicaksono; L. Abdullah (Media Peternakan, 2017)
Indigofera zollingeriana is one of legumes has a great potential to be used as an animal feed having high quality nutrients and is tolerant to different environmental conditions. The objective of this experiment was to study the effect of different row spacings between individual plants on growth pattern, forage yield, and quality of I. zollingeriana. Field experiment was conducted at Field Laboratory of Agrostology, Faculty of Animal Science Bogor Agricultural University, during the growing season of 2015/2016. The 4 spacings levels used were 1 x 1.5 m; 1 x 1 m; 1 x 0.75 m; and 1 x 0.5 m. The treatment was arranged in a completely randomized block design, with 4 replicates. Variables in this research were plant height, number of leaves, number of branches, plant population for each plot, fresh and dry matter yields, and forage quality. The results showed that narrow plant spacing increased plant height, plant population, fresh and dry weights, dry matter yields, as well as NDF and β-carotene contents. The wider the plant spacing the greater the number of branches and leaves per plant. It was concluded that increasing plant population by narrowing plant spacing remained the most effective way to increase Indigofera forage yield without negative effects of it on nutritive values, i.e., crude protein, crude fat, crude fiber, ADF, and TDN.